Soil CO2 efflux at timberline on Mt. Fuji - Kibe, Takeshi; Masuzawa, Takehiro; Awaya, Yoshio (National Institute of Polar Research, 2004)
P(論文) Soil CO2 effluxes were investigated at timberline on Mt. Fuji. Three study plots along a sequence of vegetation zones (dwarf, tall Japanese larch, and Veitch's silver fir proceeding downward) in the vicinity of timberline were selected for the measurement of soil CO2 efflux. The results showed differences in the temperature dependence of the soil CO2 efflux among the three study plots. The highest value (Q10 = 4.4) was derived at the upper plot where the vegetation and soil formation were underdeveloped. Environmental data also showed differences among the three plots in soil temperature and soil water content. The upper study plot was exposed to higher soil temperature and lower soil moisture than the other two plots because of poor vegetation cover and underdeveloped soil formation. The total soil CO2 efflux during the snow free period from June to October was estimated for the upper, middle, and lower plots as 3.3, 3.0, and 3.7 Mg C ha-1 5 months-1. The results suggest that the amount of soil CO2 efflux does not always correspond to vegetation and soil development. departmental bulletin paper